Donor-acceptor stabilized tetra(silanimine) - Shan, Yu-Liang (2020)
The synthesis of an oligo(silanimine) is described. The reaction of the amidinato silylene [LSiN(SiMe3)2] (1, L = PhC(NtBu)2) with SiI4 in toluene afforded a mixture of the silanimine [LSi(I)NSiI3] (2), SiMe3I, and Si2I6. The mechanistic studies showed that 1 reacts with SiI4 to form the silyl ionic intermediate "{LSi(I)N(SiMe3)2}+SiI3-", which then eliminates SiMe3I and "SiI2" to form the silanimine intermediate "LSi(I)NSiMe3". It further undergoes a substitution with another molecule of SiI4 to form a mixture of 2 and SiMe3I. In addition, "SiI2" undergoes an oxidative addition with SiI4 to form Si2I6. Subsequently, compound 2 reacted with [LiN(SiMe3)Ar] to form the silanimine [LSi(I)NSiI2N(SiMe3)Ar] (6, Ar = 2,6-iPr2C6H3), which was then treated with KC8 to give the donor-acceptor stabilized tetra(silanimine) [LSiN(SiMe3)SiNAr]2 (7). It comprises four formal silanimine ">Si═N-" units, which are linked together. Compounds 2, 6, and 7 were characterized by NMR spectroscopy and X-ray crystallography.